2008
DOI: 10.1002/chir.20570
|View full text |Cite
|
Sign up to set email alerts
|

Diamagnetic lanthanide tris β‐diketonates as organic‐soluble chiral NMR shift reagents

Abstract: Diamagnetic lanthanium(III) and lutetium(III) tris beta-diketonate complexes of 3-(trifluoroacetyl)-d-camphor, 3-(heptafluorobutyryl)-d-camphor, and d,d-dicampholylmethane are shown to be effective chiral NMR shift reagents for determining the enantiomeric purity of compounds with hard Lewis base functional groups. These include substrates with amine, alcohol, epoxide, sulfoxide, and oxaxolidine moieties. Enantiomeric discrimination is observed in the (1)H NMR spectrum. Diamagnetic lanthanide complexes represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The laevorotatory form ( S , S -Camphor) exists only in a synthetic form or in very little quantities in specific species of plants [ 2 ]. In chemistry, camphor has been used as a selector in chiral separations [ 3 ], as a shift reagent in nuclear magnetic resonance (NMR) [ 4 ], as a chiral auxiliary [ 5 ], and as part of a catalyst system [ 6 ] as well as a versatile chemical precursor [ 7 ]. In the medical chemistry field, studies have revealed that camphor possesses a range of useful biological activities, being an antiviral, antimicrobial, antitussive, and analgesic agent [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The laevorotatory form ( S , S -Camphor) exists only in a synthetic form or in very little quantities in specific species of plants [ 2 ]. In chemistry, camphor has been used as a selector in chiral separations [ 3 ], as a shift reagent in nuclear magnetic resonance (NMR) [ 4 ], as a chiral auxiliary [ 5 ], and as part of a catalyst system [ 6 ] as well as a versatile chemical precursor [ 7 ]. In the medical chemistry field, studies have revealed that camphor possesses a range of useful biological activities, being an antiviral, antimicrobial, antitussive, and analgesic agent [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] Furthermore, these complexes can be applied as chiral Lewis acids (CLAs) in catalytic asymmetric transformations such as hetero-Diels-Alder reactions using oxovanadium(IV) [27][28][29] or europium(III), [29][30][31][32] or asymmetric cyclopropanations using copper(II) complexes. [22][23][24][25][26] Furthermore, these complexes can be applied as chiral Lewis acids (CLAs) in catalytic asymmetric transformations such as hetero-Diels-Alder reactions using oxovanadium(IV) [27][28][29] or europium(III), [29][30][31][32] or asymmetric cyclopropanations using copper(II) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…These chiral complexes are also highly versatile chiral shift reagents in NMR spectroscopy. [22][23][24][25][26] Furthermore, these complexes can be applied as chiral Lewis acids (CLAs) in catalytic asymmetric transformations such as hetero-Diels-Alder reactions using oxovanadium(IV) [27][28][29] or europium(III), [29][30][31][32] or asymmetric cyclopropanations using copper(II) complexes. [33] The versatility of alkanoyl-camphorate metal complexes as chiral selectors in enantioselective chromatography, as chiral shift reagents in NMR spectroscopy, and as catalysts in asymmetric syntheses [34] emphasizes the importance of making these diketonate ligands easily accessible and improving their chemical properties, for example, decreasing their high volatility, which typically limits the applicable temperature range in enantioselective complexation GC.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide (Ln) complexes have a wide range of interesting applications exploiting their luminescent and magnetic properties . They are investigated for uses in areas such as catalysts for organic reactions, photosensitive glasses, sensors, and NMR shift reagents. , A particularly interesting application of Ln complexes is their in vivo use as imaging reagents through fluorescence imaging, as well as Magnetic Resonance Imaging (MRI) contrast reagents. Complexes can be injected into a tissue of interest, or ligands with cell permeable groups can allow imaging of specific tissue types . Since these complexes are used in cells it is exceedingly important that the complexes are both kinetically and thermodynamically stable especially under aqueous physiological conditions since free Ln ions are toxic. , One strategy to avoid the dissociation of lanthanide ions in solution is to employ complexes with large chelating polydentate ligands that occupy several of the Ln coordination sites.…”
Section: Introductionmentioning
confidence: 99%